Study on the effect of pressure on the thrust force of a solid propellant engine operating in a water environment - Nguyen Truong Thanh; Hoang, The Dung; Bui Dinh Tan; Bui Ngoc Lam; Nguyen Van Hung; Nguyen Huy Thanh (Journal of Military Science and Technology, 2025)
The paper presents the results of research on the impact of ambient pressure on the thrust of solid rocket engines when operating underwater at different depths. The study establishes a system of equations for rocket propulsion, considering the variations in ambient pressure while functioning in an aquatic environment. It develops algorithms and constructs a computational program for rocket propulsion in solid rocket engines operating underwater. The paper further explores how water pressure affects the engine's pressure and thrust.